2022
DOI: 10.1128/aem.00664-22
|View full text |Cite
|
Sign up to set email alerts
|

The Population Genomics of Increased Virulence and Antibiotic Resistance in Human Commensal Escherichia coli over 30 Years in France

Abstract: Escherichia coli is an opportunistic pathogen with the greatest burden of antibiotic resistance, one of the main causes of bacterial infections and an increasing concern in an aging population. Deciphering the evolutionary dynamics of virulence and antibiotic resistance in commensal E. coli is important to understand adaptation and anticipate future changes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 110 publications
(139 reference statements)
1
25
0
Order By: Relevance
“…However, there are differences in the colonization potential of E. coli lineages and the risk of invasive infection by ESBL-Ec which seems to be clone dependent. 38,41 The higher odds for infection that we detected for ST131 is similar to that of the Swedish study (AOR 3.4, 1.8-6.4) indicating a higher pathogenicity potential of ST131 compared to commensal E. coli lineages of phylogroup A, such as ST10. 13 Moreover, we found that ST131 subclade A, previously reported with less resistance, and the multidrug resistant subclade C2 had higher odds for infection, and this may contribute to the sustained establishment of these subclades among bloodstream infections in Norway.…”
Section: Discussionsupporting
confidence: 82%
“…However, there are differences in the colonization potential of E. coli lineages and the risk of invasive infection by ESBL-Ec which seems to be clone dependent. 38,41 The higher odds for infection that we detected for ST131 is similar to that of the Swedish study (AOR 3.4, 1.8-6.4) indicating a higher pathogenicity potential of ST131 compared to commensal E. coli lineages of phylogroup A, such as ST10. 13 Moreover, we found that ST131 subclade A, previously reported with less resistance, and the multidrug resistant subclade C2 had higher odds for infection, and this may contribute to the sustained establishment of these subclades among bloodstream infections in Norway.…”
Section: Discussionsupporting
confidence: 82%
“…Multiple-drug resistance in E. coli that cause extraintestinal disease can lead to increased morbidity (extended hospital stays) and mortality and has a dominant influence on the epidemiology and management of infectious disease. E. coli ST1193 has spread globally at a high rate, given that the earliest entry of ST1193 in EnteroBase is 2007 and it was absent, for example, in 403 WGS of human commensal E. coli isolates collected between 1980 and 2010 ( 23 ). Understanding virulence, however, is complex because of the redundancy in the myriad of mobile elements that carry virulence gene cargo, especially in ExPEC.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a third of the invasive ST1193 isolates studied had acquired bla CTX-M-15 , which encodes an extended spectrum of resistance to β-lactams ( 10 ). ST1193 can also persistently colonize the gastrointestinal tract of healthy women ( 3 ) but was not identified in the feces of healthy women in France prior to 2010 ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Except for ST154 and ST2858, the remaining STs described here (ST10, ST131, ST206, ST1488 and ST3576) have been previously reported. Whole-genome sequencing of a collection of 403 E. coli isolates from fecal human samples over 30 years (1980 to 2010) revealed that ST10 was one of the five major lineages among healthy humans in France [ 22 ]. ST10 was also found as the predominant clone among E. coli recovered from students in Lisbon [ 23 ] and was found among healthy and sick cats from the same geographical area as well [ 24 ].…”
Section: Discussionmentioning
confidence: 99%